Images from a jointly-arousing collective ritual reveal affective polarization - Bulbulia, Joseph A.; Xygalatas, Dimitris; Schjoedt, Uffe; Fondevila, Sabela; Sibley, Chris G.; Konvalinka, Ivana (Frontiers in Psychology, 2013)
Collective rituals are biologically ancient and culturally pervasive, yet few studies have quantified effects on participants. We assessed two plausible models from qualitative anthropology: ritual empathy predicts affective convergence among all ritual participants irrespective of ritual role; rite-of-passage predicts emotional differences, specifically that ritual initiates will express relatively negatively valence when compared with non-initiates. To evaluate model predictions, images of participants in a Spanish fire-walking ritual were extracted from video data and assessed by nine Spanish raters for arousal and valence. Consistent with rite-of-passage, we found that arousal jointly increased for all participants but that valence differed by ritual role: fire-walkers exhibited increasingly positive arousal and increasingly negative valence when compared with passengers. This result offers the first quantified evidence for rite of passage dynamics within a highly arousing collective ritual. Methodologically, we show that surprisingly simple and non-invasive data structures (rated video images) may be combined with methods from evolutionary ecology (Bayesian Generalized Linear Mixed Effects models) to clarify poorly understood dimensions of the human condition.